Annual Report and Accounts for the year ended 30th June, 1983 (The Southern African Institute of Mining and Metallurgy, 1983)
Council and Standing Committees - 1982/83 President: Prof. A. N. Brown Vice Presidents: Prof. R. P. King and J. D. Austin Honorary Treasurer: Prof. D. G. Krige Immediate Past President: G. Y. Nisbet Members of Council: B. C. Alberts, R. H. English, P. T. Fewell, C. E. Fivaz, J. S. Freer, Prof. G. G. Garrett, J. J. Geldenhuys, Dr A. K. Haines, P. N. Harris, H. E. James, Dr B. K. Loveday, Dr J. Lurie, D. G. Malan, G. Pienaar, B. E. Protheroe, Dr 0. K. H. Steffen, G. C. Thompson, Dr H. Wagner, Dr P. T. Wedepohl. Chairman, Witbank/Middelburg Branch: H. C. van Zyl.